Verbal and conceptual aspects of the methodological discourse VII convent RISA - V. S. Glagolev (Vestnik MGIMO-Universiteta)
The article highlights some of the key concepts in the analysis of the international process, the use of which requires a systematic semantic correctness. Demonstrated graphically and ideological phenomena arising from a breach of this requirement.